Research of the Method and Test Bench of Drive Axle Transmission Efficiency for Heavy Vehicle - Zhan Rui; Cheng Huaguo; Li Jun; Xu Kang; Shen Chao (Jixie chuandong)
In order to satisfy the test requirements of transmission efficiency of heavy vehicle drive axle,the test bench of transmission efficiency for heavy vehicle drive axle is designed. The structure,principle and the key parts of the test bench are introduced. Aiming at the problem of the lack of heavy vehicle drive axle transmission efficiency industry test standards in domestic,a test method for heavy vehicle drive axle transmission efficiency is presented referring to the test standard QC / T533- 1999 Vehicle Axle Bench Test Methods and QC / T568. 1- 2011 Vehicle Mechanical Gearbox Assembly Bench Test Methods Part 1: Minicar and combining with heavy vehicle drive axle actual working conditions in domestic. Then the transmission efficiency test for a heavy vehicle drive axle is conducted. The test indicates that the test bench has a superior controlling accuracy and measuring precision and can fully meet the test requirements.